The Correlation of Knowledge Level with Occupational Health and Safety (OHS) Behaviour of Using Pesticides in Asparagus Farmers - Negara, Ni Luh Gede Aris Maytadewi; Jaya, I Putu Prisa; Suandari, Putu Vierda Lya (GLOBAL HEALTH SCIENCE GROUP, 2024)
The use of pesticides in agriculture is not a new thing anymore. The use of pesticides by farmers aims to protect crops from pests. The use of pesticides by farmers is an activity that is included in a work assignment, so that to minimize the negative impact caused by pesticides, the use should be carried out according to healthy and safe procedures. The limited knowledge and understanding of farmers about the dangers of pesticides and not using work equipment that meets occupational safety and health standards are some of the factors that cause health problems due to exposure to pesticides to farmers. This study aims to determine the correlation between the level of knowledge and the Occupational Health and Safety (OHS) behaviour of pesticide use in asparagus farmers. This study is quantitative research using analytical survey research methods, with cross sectional. The population in this study were asparagus farmers in Pelaga Village, Badung who routinely sprayed, with a sample of 63 people who were taken by purposive sampling technique. Data collection was carried out by giving questionnaires to farmers, and data analysis was carried out by using the test Chi-Square. As many as 42 people (66,7%) farmers have a good level of knowledge about pesticides, 40 people (63.5%) have a safe behaviour in the use of pesticides, and the chi-square test obtained a positive correlation with the value of P= 0.026(p<0.05). This shows that there is a corelation between the level of knowledge and the Occupational Health and Safety behaviour of pesticide use in asparagus farmers.